1996
DOI: 10.1089/neu.1996.13.85
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Difluoromethylornithine Treatment on Regional Ornithine Decarboxylase Activity and Edema Formation after Experimental Brain Injury

Abstract: This study examined the effect of difluoromethylornithine (DFMO) on regional activities of ornithine decarboxylase (ODC) and edema formation in bilateral cerebral cortex and hippocampus after a unilateral controlled cortical-impact (CCI) injury in rats. To measure the activity of ODC, the brains of injured and control rats were frozen in situ at 30 min, 3, 6, and 24 h after CCI brain injury of moderate severity. The specific gravity, an indicator of edema formation, was examined in decapitated animals at corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…A␤ is shown to oxidize numerous neuronal proteins (Aksenov et al, 1997;Butterfield, 1997;Yatin et al, 1998Yatin et al, , 1999bButterfield et al, 1999). In previous studies polyamine biosynthesis inhibitors were reported as neuroprotective agents (Kindy et al, 1994;Baskaya et al, 1996). These agents may protect the neurons from overaccumulation of polyamines to toxic levels by inhibiting the specific enzymatic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…A␤ is shown to oxidize numerous neuronal proteins (Aksenov et al, 1997;Butterfield, 1997;Yatin et al, 1998Yatin et al, , 1999bButterfield et al, 1999). In previous studies polyamine biosynthesis inhibitors were reported as neuroprotective agents (Kindy et al, 1994;Baskaya et al, 1996). These agents may protect the neurons from overaccumulation of polyamines to toxic levels by inhibiting the specific enzymatic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Regional changes in ODC activity correlated with edema formation after traumatic brain injury. In another study DFMO treatment decreased omithine decarboxylase activity and edema formation after experimental brain injury (Baskaya et al, 1996b). However, changes in putrescine or polyamines were not measured after injury.…”
Section: Introductionmentioning
confidence: 94%
“…Difluoromethylornithine (DFMO) was synthesized almost 30 years ago as an irreversible inhibitor of ornithine decarboxylase (ODC). It was shown that DFMO decreased edema after cortical impact (5) and ischemic injury volume after experimental cerebral ischemia (3). Our earlier work showed that DFMO treatment reduced radiation-induced necrosis, vascular permeability and associated vasogenic edema after focal radiation-induced injury (68).…”
Section: Introductionmentioning
confidence: 99%